Harmoni dan Toleransi: Menyelami Hubungan antar Agama dalam Perspektif Pandangan Dunia Islam - Sugiyarti, Sri; Mujahid, Kasori (Lembaga Yasin AlSys, 2024)
This article discusses the importance of harmony and tolerance in establishing interfaith relations, especially in the context of the Islamic worldview. The author explores key concepts in Islam that encourage harmony between religious believers, as well as delving into aspects that promote understanding and respect for differences in beliefs. The article also highlights the history and practices that support interfaith harmony in Islamic societies. In conclusion, harmony and tolerance are considered central values in Islam, and this article invites readers to explore them more deeply from the perspective of the Islamic worldview.